Higher levels of plasma phosphatidylcholine (17:0_18:1) raise the risk of developing Parkinson’s disease - Daoqing Su; Yajun Jing; Jinye Su; Honglin Zhu; Yiming Chen; Qiu He; Dengliang Wang; Dezhi Kang; Yuanxiang Lin (Scientific Reports)
Abstract Emerging evidence suggests that dysregulation of lipid metabolism and chronic inflammation in the central nervous system (CNS) contribute to the risk of Parkinson’s disease (PD). However, the causal relationship between plasma lipid metabolism and PD, particularly through immune modulation, remains unclear. In this study, we used Mendelian randomization (MR) to investigate the causal association between plasma lipidome and PD risk, utilizing GWAS summary statistics for PD, circulating immune cells, inflammatory proteins, and plasma lipidome. We found that higher plasma phosphatidylcholine (17:0_18:1) levels were causally associated with an increased risk of PD, with a 1 standard deviation genetically instrumented higher level corresponding to a 30% increased risk (95% CI 1.05–1.61, p = 0.014). Multivariate Mendelian randomization (MVMR) analysis confirmed this association after adjusting for triacylglycerol levels. Mediation analysis revealed that the causal link between plasma phosphatidylcholine and PD was mediated by circulating immune cells (specifically CD45 on CD14+ monocytes and CD45 on HLA-DR+ T cells) rather than by circulating inflammatory proteins. These findings highlight a novel pathway linking lipid metabolism, immune modulation, and PD risk.